Women's Suffrage in Indonesia: A Structural Analysis of Women's Representation in Parliament - Umbase, Ruth Sriana; Sumilat, Grystin; Mesra, Romi (Technium Social Sciences Journal, 2023)
This study aims to analyze the meaning of women's suffrage through the representation of women in parliament in Indonesia. The Research method used is A Structural Analysis of the Historical Research Method. The study results show that the meaning of women's suffrage in Indonesia, especially in the political field, means the right to vote and be elected. Every woman who has the right to vote can use her right to vote freely, but women who have been successfully elected "to sit in parliament" have not been equal and balanced in number compared to men. The lowest gender empowerment index is the involvement of women in parliament; nevertheless, in the period 2019-2022, there has been an increase. This condition will certainly affect the next period if political parties can consistently carry out affirmative action and other interventions based on gender equality. There is a need to strengthen a gender-responsive political paradigm through various training forums on gender mainstreaming for leaders and members of political parties continually.